Teleworking in Times of COVID-19: Effects on the Acquisition of Personal Resources - Pulido-Martos, Manuel; Cortés-Denia, Daniel; Lopez-Zafra, Esther (Frontiers in Psychology, 2021)
The COVID-19 pandemic has forced many employees to introduce different degrees of teleworking, leading to a transformation of the psychosocial work environment. In this study, we analyzed whether the relationship between a labor resource, social support, and a personal resource, vigor at work, is affected by the work modality (face-to-face, hybrid that includes face-to-face work and telework time, and telework caused by the current pandemic situation). Five hundred and forty-three employees answered an online questionnaire about their perceptions of the levels of social support, vigor experienced in the last month, and work modality. Seniority in the organization and the gender of the employees were controlled for. The model fit was significant [F(7, 535) = 20.816, p < 0.001], accounting for 21% of the variation in vigor (R2 = 0.21). The interaction was also significant [F(2, 535) = 4.13, p < 0.05], with an increase of 1% in the explanation of the variance in vigor at work (ΔR2 = 0.01). Differences were found in the positive relationship between levels of social support and vigor at work, among the face-to-face and telework modalities (hybrid and telework), but not between teleworking modalities. As a result, we posit that the different forms of telework moderate (buffer) the relationship experienced between labor resources (social support) and personal resources (vigor at work). This implies that, for the design of teleworking conditions, it is necessary to provide work resources similar to those in face-to-face settings, such as social support.